A reporter cell system for the triggering receptor expressed on myeloid cells 2 reveals differential effects of disease‐associated variants on receptor signaling and activation by antibodies against the stalk region. Issue 5 (14th December 2020) - Ibach, Melanie; Mathews, Mona; Linnartz‐Gerlach, Bettina; Theil, Sandra; Kumar, Sathish; Feederle, Regina; Brüstle, Oliver; Neumann, Harald; Walter, Jochen
Abstract: The triggering receptor expressed on myeloid cells 2 (TREM2) is an immune receptor expressed on myeloid‐derived cell types. The extracellular immunoglobulin‐like domain of TREM2 binds anionic ligands including Apolipoprotein E and Amyloid‐β. The transmembrane domain interacts with its adaptor protein DAP12/TYROBP that is responsible for propagation of downstream signaling upon ligand interaction. Several sequence variants of TREM2 have been linked to different neurodegenerative diseases including Alzheimer's disease. Here, we generated HEK 293 Flp‐In cell lines stably expressing human TREM2 and DAP12 using a bicistronic construct with a T2A linker sequence allowing initial expression of both proteins in stoichiometric amounts. Cell biological and biochemical analyses revealed transport of TREM2 to the cell surface, and canonical sequential proteolytic processing and shedding of TREM2 (sTREM2). The functionality of this cell system was demonstrated by detection of phosphorylated spleen tyrosine kinase (SYK) upon stimulation of TREM2 with the anionic membrane lipid phosphatidylserine or anti‐TREM2 antibodies. Using this cell model, we demonstrated impaired signaling of disease associated TREM2 variants. We also identified a monoclonal antibody against the stalk region of TREM2 with agonistic activity. Activation of TREM2‐DAP12 signaling with the monoclonal antibody and the partial loss of function of disease associated variants were recapitulated in induced pluripotent stem cell derived microglia. Thus, this reporter cell model represents a suitable experimental system to investigate signaling of TREM2 variants, and for the identification of ligands and compounds that modulate TREM2‐DAP12 signaling. MAIN POINTS: Disease associated variants impair the signaling activity of TREM2 by distinct mechanisms. Targeting the stalk region of TREM2 with bivalent antibodies activates TREM2 signaling. Main Points: Disease associated variants impair the signaling activity of TREM2 by distinct mechanisms. Targeting the stalk region of TREM2 with bivalent antibodies activates TREM2 signaling.